Evaluation of Bi-Lateral Co-Infections and Antibiotic Resistance Rates among COVID-19 Patients in Lahore, Pakistan - Azka Rizvi; Muhammad Umer Saeed; Ayesha Nadeem; Asma Yaqoob; Ali A. Rabaan; Muhammed A. Bakhrebah; Abbas Al Mutair; Saad Alhumaid; Mohammed Aljeldah; Basim R. Al Shammari; Hawra Albayat; Ameen S. S. Alwashmi; et al. (Medicina, 2022)
Background and Objective: Bacterial infections are among the major complications of many viral respiratory tract illnesses, such as influenza and coronavirus disease-2019 (COVID-19). These bacterial co-infections are associated with an increase in morbidity and mortality rates. The current observational study was conducted at a tertiary care hospital in Lahore, Pakistan among COVID-19 patients with the status of oxygen dependency to see the prevalence of bacterial co-infections and their antibiotic susceptibility patterns. Materials and Methods: A total of 1251 clinical samples were collected from already diagnosed COVID-19 patients and tested for bacterial identification (cultures) and susceptibility testing (disk diffusion and minimum inhibitory concentration) using gold standard diagnostic methods. Results: From the total collected samples, 234 were found positive for different bacterial isolates. The most common isolated bacteria were Escherichia coli (E. coli) (n = 62) and Acinetobacter baumannii (A. baumannii) (n = 47). The E. coli isolates have shown the highest resistance to amoxicillin and ampicillin, while in the case of A. baumannii, the highest resistance was noted against tetracycline. The prevalence of methicillin resistant Staphylococcus aureus (MRSA) was 14.9%, carbapenem resistant Enterobacteriaceae (CRE) was 4.5%, and vancomycin resistant Enterococcus (VRE) was 3.96%. Conclusions: The results of the current study conclude that empiric antimicrobial treatment in critically ill COVID-19 patients may be considered if properly managed within institutional or national level antibiotic stewardship programs, because it may play a protective role in the case of bacterial co-infections, especially when a patient has other AMR risk factors, such as hospital admission within the previous six months.